Isolation, biochemical characterrization and identification of microorganisms from spoilt tomatoes obtained from local markets of Dhaka city, Bangladesh - Chowdhury, Mahzabeen (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.